Validation of the FACT-G7 in patients with hematologic malignancies - Du, Xinwen; Mao, Ling; Leng, Yamei; Chen, Fengjiao (Frontiers in Oncology, 2023)
Background: It is essential to evaluate the quality of life in patients with hematologic malignancies to reflect the therapeutic effect and prognosis, but lengthy assessments are often burdensome. The 7-Item Functional Assessment of Cancer Therapy-General (FACT-G7) is a brief, easy, and rapid index for evaluating quality of life. Nevertheless, there is no report about its application in Chinese patients with hematologic malignancies. Objective: The purpose of this study was to validate the Chinese version of the FACT-G7 for patients with hematologic malignancies. Methods: This study is a cross-sectional study. A total of 855 patients with hematologic malignancies completed the Functional Assessment of Cancer Therapy-General (FACT-G) and were scored the Eastern Cooperative Oncology Group Performance Status (ECOG-PS) by nurses. Cronbach’s alpha, confirmatory factor analyses, Pearson’s correlation, and one-way analysis of variance were conducted to evaluate internal consistent reliability, structural validity and concurrent validity. Results: The FACT-G7 showed acceptable internal consistency, as indicated by a Cronbach’s alpha of 0.73. The confirmatory factor analyses test for single-factor model fit for the FACT-G7 scale was almost adequate. The satisfactory correlations between the FACT-G7 and the FACT-G and its subscales, and ECOG-PS groups differed in FACT-G7 scores demonstrating concurrent validity. Conclusions: This study suggested that the Chinese version of the FACT-G7 provides a useful and rapid measure for assessing quality of life in Chinese patients with hematologic malignancies, which providing a reference for further evaluation and care.